Meningkatkan Hasil Belajar Pendidikan Agama Katolik dengan Model Problem Based Learning (PBL) Fase C Kelas V SDN 105302 Tangkahan - Maria Indah Marbun; Dicky Aprianto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Education is simply defined as human efforts to nurture and develop innate potential both physically and spiritually in accordance with the values present in their society and culture. The Merdeka Curriculum is a curriculum with diverse intracurricular learning and improved content, allowing students sufficient time to learn concepts and strengthen skills. The purpose of Catholic Religious Education in schools is to encourage students to interact or communicate in understanding, confronting, and living their faith. However, at SDN 105302 Tangkahan, there are challenges in teaching Catholic Religious Education, namely the low learning outcomes of students due to more conventional and non-interactive teaching methods. There is a lack of use of engaging learning media and technology that is considered irrelevant to students' daily lives. This research aims to improve student learning outcomes in Catholic Religious Education through the application of the Problem Based Learning (PBL) model. This study uses a classroom action research method with fifth-grade students in phase C at SDN 105302 Tangkahan as research subjects. Data was collected through observation, tests, and interviews. The results show a significant improvement in concept understanding, collaboration skills, and student learning outcomes after the implementation of the PBL model in Catholic Religious Education.